Effect of potato extract on in vitro seed germination and seedling growth of local Vanda roxburgii orchid - Islam, MO; Akter, M; Prodhan, AKMA (Journal of the Bangladesh Agricultural University, 2012)
An experiment was conducted to investigate the effect of potato extract (PE) on seed germination and seedling growth of Vanda roxburgii in vitro, a local orchid. Potato extracts significantly enhanced seed germination and seedling growth. Among the concentrations, PE at 200 mlL-1 enhanced per cent germination from 17.2% (control) to 78.24% and was found to be the most suitable one for seed germination. It was also the best among treatments for production of viable protocorms as well as healthy seedlings from seeds. Growth of seedlings in respect of length of shoot, number of root per shoot and length of root per seedling was significantly enhanced in medium supplemented with 100 mlL-1 of PE. It may be concluded that PE at optimum concentration could be supplemented in medium for high percentage of seed germination and seedling growth of Vanda orchid. DOI: http://dx.doi.org/10.3329/jbau.v9i2.10988 J. Bangladesh Agril. Univ. 9(2): 211215, 2011